2021
DOI: 10.3390/met11071142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging under Stress on Mechanical Properties and Microstructure of EN AW 7075 Alloy

Abstract: In the present study, microstructural and mechanical properties of EN AW 7075 following stress-aging were assessed. For this purpose, properties of stress-aged samples were compared with values obtained for conventionally aged counterparts. It is revealed that the strength and hardness of EN AW 7075 can be increased by the presence of external stresses during aging. Precipitation kinetics were found to be accelerated. The effects of conventional and stress-aging on the microstructure were analyzed using synerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 68 publications
(91 reference statements)
0
17
0
Order By: Relevance
“…The electron-transparent specimens and d) schematic highlighting the process (Reproduced under terms of the CC-BY license. [17] Copyright 2022, S.V. Sajadifar et al, published by Metals).…”
Section: Analysis Of Microstructurementioning
confidence: 99%
See 3 more Smart Citations
“…The electron-transparent specimens and d) schematic highlighting the process (Reproduced under terms of the CC-BY license. [17] Copyright 2022, S.V. Sajadifar et al, published by Metals).…”
Section: Analysis Of Microstructurementioning
confidence: 99%
“…[15,16] Recently, novel thermomechanical treatments were employed to further improve the mechanical behavior of EN AW-7075 alloy. [12][13][14]17] Stress aging was found to be capable of enhancing the mechanical properties. [17,18] Previous studies showed that external stress or strains induced during aging considerably accelerate the precipitation kinetics, [17,18] as this approach can provide additional nucleation sites for precipitates.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The T6 heat treatment, i. e. solution heat treatment followed by water quenching and subsequent artificial aging, can considerably enhance the strength of EN AW 7075 alloy [3]. Generally, the ultimate tensile strength of EN AW 7075 alloy in T6 condition was reported to be above 500 MPa, which is the highest value among the commercially available high-strength aluminum alloys [4][5][6][7]. In addition to the high ultimate tensile strength of this alloy, its acceptable formability in temperature-supported forming processes makes it a promising alternative for numerous engineering demands [8].…”
Section: Introductionmentioning
confidence: 99%